INFOGRAPHIC AND RELIGIOUS CONTENT TO IMPROVE STUDENTS’ ABILITY CONSTRUCTING CAUSE EFFECT RELATIONSHIP - Fadhly Tanjung; Purwanto Siwi; Irma Khoirot Daulay (Universitas Islam Sumatera Utara, 2022)
This research is aimed at elucidating the improving of students’ ability in constructing cause effect sentences using Islamic content blended to one of multimodality teaching called infographic. This research is applied on tourism regular class X of SMK Negeri 8 Medan in 2020 where 30 students participated as subject of the research. This class action research is conducted in two main cycles namely planning, conducting, observing and reflecting where all are implemented separately in both cycles. Collection of the data is taken through observation sheet, result of the test and documentation of activity and infograhic result. The using of infographic not only could increase the ability of students to construct sentences containing cause effect relationship but also trigger their interest and maintain their motivation to participate actively during learning hours, and religious content itself is to call back students’ knowledge about why something is obliged or forbidden in Islam. The results show that students level of participation to actively get involved in learning cause effect sentences in first cycle reaches 60% while average learning outcomes is 60%. Then in second cycle the participation increases to 75% and average learning outcomes exceed 75%. Thus, using infographic is very useful to increase students’ ability in constructiong cause effect sentences.